Ἔθνη Θρᾳκῶν στὴ Θράκη τοῦ Αἰγαίου κατὰ τοὺς ἑλληνιστικοὺς καὶ ρωμαϊκοὺς χρόνους I. Κορπίλοι καὶ Κορπιλική - Παρισάκη, Μαρία-Γαβριέλλα (Tekmeria, 2021)
Of two articles devoted to the Thracian tribes attested in Aegean Thrace during the Hellenistic and Roman periods, the first, published here, focuses on the tribe of the Corpiloi (the second article, under the title ‘Ἔθνη Θρᾳκῶν στὴ Θράκη τοῦ Αἰγαίου κατὰ τοὺς ἑλληνιστικοὺς καὶ ρωμαϊκοὺς χρόνους, ΙΙ. Σαπαῖοι καὶ Σαπαϊκή’, devoted to the Sapaioi, will be published in the following volume of Τεκμήρια). The relevant testimonia, exclusively literary, range from the first century BC ‒or the beginning of the second century BC, for those who accept the emendation Coreli-Corpili in the text of Livy‒ to the beginning of the second century AD. They consist of short references in Strabo, Pliny the Elder, and Solinus, a reference to the στενὰ τῶν Κορπίλων by Appian in conjunction with the battle of Philippi in 42 BC, as well as a reference to a Κορπιλικὴ στρατηγία in Claudius Ptolemy. The present article tries to define Corpiloi’s localization, suggesting the lower course of the Hebrus river, mainly to the west but also, possibly, to the east of the river, up to the north of Ainos. In view of their relatively short emergence in ancient sources, the article also addresses the question of Corpiloi’s relation to the region’s major tribes, namely the Odrysai and the Sapaioi. Finally, a brief and preliminary overview of the region’s archaeological map indicates integration into the region’s wider cultural sphere.